2012
DOI: 10.1097/id.0b013e31824885b5
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cone Beam Computed Tomography in Implant Dentistry

Abstract: The literature supports the use of CBCT in dental implant treatment planning particularly in regards to linear measurements, three-dimensional evaluation of alveolar ridge topography, proximity to vital anatomical structures, and fabrication of surgical guides. Areas such as CBCT-derived bone density measurements, CBCT-aided surgical navigation, and postimplant CBCT artifacts need further research. ICOI RECOMMENDATIONS: All CBCT examinations, as all other radiographic examinations, must be justified on an indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(76 citation statements)
references
References 44 publications
(15 reference statements)
0
67
0
3
Order By: Relevance
“…In recent years, dental CT has been widely used in dental clinical practices mainly because dental CT is not only inexpensive and involves low radiation doses [18], [29], [30], but it also possesses higher spatial resolutions for precisely measuring bone shapes and contours than traditional computed tomography does. Hashimoto et al [31] indicated that both the magnification and distortion of dental CT are extremely small (error < 0.1 mm).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, dental CT has been widely used in dental clinical practices mainly because dental CT is not only inexpensive and involves low radiation doses [18], [29], [30], but it also possesses higher spatial resolutions for precisely measuring bone shapes and contours than traditional computed tomography does. Hashimoto et al [31] indicated that both the magnification and distortion of dental CT are extremely small (error < 0.1 mm).…”
Section: Discussionmentioning
confidence: 99%
“…An adequate determination of the bone height is recommended for avoiding the potential risks of intrusion of implants into vital anatomical structures including nerves, blood vessels, and impacted or supernumerary teeth 17. The buccolingual width and angulation of the available bone are the most important criteria for implant selection and success.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 As the BMD can be measured by non-destructive X-ray-based technology, it is also utilized to diagnose bone disease and estimate bone quantity and quality of dental implantation sites in the clinical settings. 6,12,13 Bone is a heterogeneous material consisting of minerals on a collagen matrix. 14,15 The composition of bone changes by modelling and remodelling processes, which are activated at different time points.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] As the CBCT is an X-ray-based device, the dense materials of hard tissues (i.e. bone and tooth) absorb more radiation energy than soft tissues (i.e.…”
Section: Introductionmentioning
confidence: 99%